TRANSFORMASI ARSITEKTUR PERMUKIMAN TRADISIONAL DI JAWA DARI MASA HINDU-BUDHA KE MASA ISLAM - Rahadhian PH (Research Report - Engineering Science, 2008)
Hindu-Buddha period in Java was identical with the period when Indonesia was still influenced by Hinduism and Buddhism traditions or the syncretism i.e. Siva Buddha; around 4th century – 15 AD. The kingdoms which had strong influences in that period were Hindu-Buddha Mataram-Sailendra-Sanjaya until Majapahit. Settlements in this period were only being able to be seen on the relief carved on the wall of temples of the eras. In Java, in 15th century after the end of Majapahit Kingdom, there was an authority transition from Hindu-Buddha style to Islamic, by the existence of Demak-Pajang Kingdom and Islamic Mataram Kingdom. The settlements that are known until now are reckoned to be started from Mataram-Islam Kindgom and then become the basics of Javanese traditional architecture knowledge. Traditional architecture of this period was different from the description of Hindu-Buddha period, although in the cultural context, Majapahit period traditions still influenced significantly in Islamic Mataram period by enculturation. This study concerns architecture transformation of settlements in the two eras because of cultural transition, which can be observed until now. The architecture transformation can be noticed in building forms and arrangement patterns; settlements in urban context. The example of Hindu-Buddha settlements architecture in Java which based on the relief is the raised floor-platform with geometrical settlements pattern, which was abandoned in Islamic Mataram period, although the geometrical pattern was still used. The platform transformation to be a non-raised floor was estimated to be happened in Majapahit period. Based on archeologically found buildings of Majapahit period, some buildings had platforms, some others did not have. The transformation was possibly influenced by foreign countries along with the entries of new belief systems or new architecture styles, as the results of international relationships development, which slowly changed the settlements images, e.g. the influence of Chinese architecture style. Besides the lower part of building, the roof was also noticed to have changes from gable-hip/saddle roof to hip and at last became “joglo” (stacked hip roof). In Hindu period temple’s relief, there were no joglo roof form; so that it can be acknowledged that the roof type did not come from old tradition, but a new form of roof, which then became one of the icons of Javanese traditional roof form. The rooms inside the building also showed the transformation. In Java, recently, it is difficult to see genuinely the settlements pattern which still shows Majapahit characteristics. However, as the comparison to it, those in Bali will be used. Based on historical studies, Hindu-Majapahit influences is still there in Bali until now. The real form of settlements pattern of temple relief can still be seen in Bali, although there has been a modification, however, the traditional pattern trails can still be noticed. The architecture and settlements pattern transformations are related closely to the urban cultural transitions. Between traditiononal architecture of settlements in Hindu period and Islamic period, there are differences between the form and space (room and building), although there are still same things; an element which has been abandoned, while the other is still developed. Is there a spatial transformation which is caused by the spiritual transformation from Hindu period to Islamic period? This matter will be deeply studied through a history exploration. The purpose of this study is to examine the correlation between both of them, together with elements transformation and their correlations in urban scale, just like theirs with other functions such as worshipping places, palaces, and so on. Key word : Transformation, hip-roof, saddle-roof, raised floor-platform